FAKTOR PENDORONG DAN PENGHAMBAT PROSES ISLAMISASI DI INDONESIA - Putri, Farah Nadiyah; Warohma, Mawadda; Calia, Risna; Maulidia, Wafiqoh (Universitas Islam Syekh-Yusuf, 2022)
Islam came to Indonesia since the 7th century through Muslim traders and merchants who made trade contacts in the archipelago. This study discusses the factors driving and inhibiting the process of Islamization in Indonesia. This study uses a library research method whose sources are obtained through books and previous studies which are used as data samples and research instruments. The process of Islamization that occurred in the territory of Indonesia did not always run well. In addition to the many things that support the process of spreading Islamization, there are also those that hinder the process of spreading Islam due to the influence of various aspects. Behind the easy process of accepting Islam in the territory of Indonesia that occurs through various channels of Islamization, the obstacles experienced also have a major influence, resulting in the acceptance of Islam which is not equally welcomed by several community groups who are still thick with previous teachings and beliefs. Keywords : Islamization, Islam, Indonesia